Microwave-Controlled Spectroscopy Evolution for Different Rydberg States - Yinglong Diao; Haoliang Hu; Xiaofei Li; Zhibo Li; Feitong Zeng; Yanbin Chen; Shuhang You (Photonics)
In this paper, a series of electromagnetically-induced-transparent (EIT) spectra of different Rydberg states, controlled by microwaves, in rubidium (Rb) thermal vapor are presented. The novel evolution regularity for different Rydberg states can be found by experimentally detected transmitted EIT spectra, which can reveal the primary quantum number of different Rydberg states and how to influence microwave control spectroscopy evolution regularity, and which can pave the way in order to address the challenge of selecting Rydberg states for applications in Rydberg microwave field detection. This is helpful for the development of measuring standards of the microwave field in Rydberg states.